The electronic behavior of zinc-finger protein binding sites in the context of the DNA extended ladder model - Oiwa, Nestor Norio; Cordeiro, Claudette E.; Heermann, Dieter W. (Frontiers in physics, 2016)
Instead of ATCG letter alignments, typically used in bioinformatics, we propose a new alignment method using the probability distribution function of the bottom of the occupied molecular orbital (BOMO), highest occupied molecular orbital (HOMO) and lowest unoccupied orbital (LUMO). We apply the technique {\color{red} to transcription} factors with Cys2His2 zinc fingers. These {\color{red} transcription} factors search for binding sites, probing for the electronic patterns at the minor and major DNA groves. The eukaryotic Cys2His2 zinc finger proteins bind to DNA ubiquitously at highly conserved domains. They are responsible for gene regulation and the spatial organization of DNA. To study and understand these zinc finger DNA-protein interactions, we use the extended ladder in the DNA model proposed by Zhu, Rasmussen, Balatsky & Bishop (2007) \cite{Zhu-2007}. Considering one single spinless electron in each nucleotide $π$-orbital along a double DNA chain (dDNA), we find a typical pattern for the bottom of BOMO, HOMO and LUMO along the binding sites. We specifically looked at two members of zinc finger protein family: specificity protein 1 (SP1) and early grown response 1 transcription factors (EGR1). When the valence band is filled, we find electrons in the purines along the nucleotide sequence, compatible with the electric charges of the binding amino acids in SP1 and EGR1 zinc finger.